Kepatuhan Pedagang Pasar Raya Dalam Penerapan Protokol Kesehatan Pencegahan Covid-19 - Gusni Rahma; Yulia (JURNAL KESEHATAN MERCUSUAR, 2022)
There were 248 cases of Covid-19 among traders in Padang City. The application of health protocols to traders is still low at 44.1%. The strategy in breaking the chain of transmission of Covid-19 is by implementing health protocols, especially in the market. The strategy in breaking the chain of transmission of Covid-19 is by implementing health protocols in daily life, especially in public places such as markets. The purpose of this study was to determine the factors related to the compliance of Pasar Raya traders in the application of the Covid-19 preventive health protocol. The study used a quantitative approach with a cross sectional study design. The dependent variable is the application of health protocols. The independent variables are age, gender, education, knowledge, attitudes and sources of information. Samples were taken purposively as many as 100 respondents according to the inclusion criteria. Collecting data using a questionnaire on traders at Pasar Raya Padang. Multivariate analysis using logistic regression. The results of the study found that 68% of traders did not comply in implementing the Covid-19 prevention health protocol. The most influential variable with compliance in the application of health protocols is knowledge with a POR of 3.29 (95% CI 1.27-8.56), meaning that traders who have low knowledge have 3.29 times the opportunity to be disobedient in implementing the COVID-19 preventive health protocol. compared to traders who have high knowledge. Continuous education is needed to market traders regarding the benefits of implementing health protocols to break the chain of transmission of Covid-19. Keywords: Covid-19; health protocol; traders; obedience